Lipschitz continuity of an approximate solution mapping for parametric set-valued vector equilibrium problems. (3rd May 2016) - Sadeqi, I.; Salehi Paydar, M.
Abstract : The purpose of this paper is to generalize and improve some topological properties of solutions set to the set-valued vector equilibrium problems by using the scalar characterization method. Moreover, the Lipschitz continuity of an approximate solution mapping for the parametric set-valued vector equilibrium problems is studied.